Research on Market Trends and Consumer Behavior in Male Grooming Products ( Especially Face Cleanser Category ) in Indonesia - Herdiyanti, Nindita; Titus, Amol (The Indonesian Journal of Business Administration, 2013)
There is an emerging trend of male who also concern about their looks and appearance, not in a feminine way, but more to that now they are realizing that male have different needs compare to female. This trend is happening across the globe, including Indonesia. Nielsen’s data shows 13.5% growth of the Indonesian market value of male grooming products from 2010 to 2011, growth on household expenditure, higher purchase frequency and volume per trip on male grooming product. Nielsen’s home panel data also shown that among all personal care categories, the growth mostly comes from male segment, especially from the face cleanser category followed by shampoo. While these significant growth happened on the male grooming segment until 2010, there was a survey conducted by Maxus 3D Data in 2011 stated that almost half (41%) of the Indonesian male are currently still using the facial cleanser for female. Relating these two contradictory facts, it seems that this will be an issue for all manufacturers which already launched the specific male products to the market because they will not accept maximum profit. This final project purposes is to find out first the trend and male consumer behavior towards face cleansers product, identifying why there are still some men using the non male brands although there are many specific product for male available and identify key success factors that facial cleansers brands must consider to succeed with male consumers.  There are three methods to answer those questions, first is literature review on consumer behavior, branding, and the current condition of Indonesian male grooming market – specifically face cleanser category. The second one is data collecting using quantitative (questionnaire) and quantitative (FGD and expert interview) methods and by doing the market observation. The results shows that face cleansers is a very potential market in Indonesia and almost 80% of the respondents are using the category nowadays. Before companies actively playing on this face cleansers male category, brand is not considered as an important element. Male will use any brands available at their home as long as it is able to solve their skin problems. Now, higher advertising spending on this category is actually seen, mainly to increase the consumer’s awareness. Comparing the Maxus 3D Data 2011 with the study result, it seems that more and more male are using the male brands although the increment is not significant. Those who are still using the non male brands find there is no need to use specific male brands as long as their current brands are effective and suitable for their skin. The product is also already available at their home so that there is no need to spend additional money for buying other product. The recommendation from significant others are also affecting their decision making process. From the small segmentation, observed that there are also some differences in terms of place of purchase preferences, brand consideration, brand endorsers, and occasions of using face cleansers product among the upper social economic class versus lower economic class consumers. In terms of brand preference, Ponds, Biore Men, L’oreal Men Expert and Vaseline Men are the 4 top brands which doing well in terms of level of usage among consumers with different strong perception correlating with each of them. One product image that considered as the most important thing is preventing acne which is now owned by the non male brand, Clean and Clear. Educating male consumers that their skin is actually different with female is the main homework for all personal care companies. In order to be success on grabbing the attention from the male consumers in Indonesian urban market, some recommendations are given based on the 4P marketing mix strategies, from product, place, promotions, and price point of view. As this will also be an input to Millward Brown report for Unilever, there are some suggestions in terms of do’s and don’ts for them divided by each social economic class segments. Keywords: outsourcing, project management, project management office.